Factors associated with loss to follow up among HIV-exposed children: a historical cohort study from 2000 to 2017, in Porto Alegre, Brazil - Karen da Silva Calvo; Daniela Riva Knauth; Bruna Hentges; Andrea Fachel Leal; Mariana Alberto da Silva; Danielle Lodi Silva; Samantha Correa Vasques; Letícia Hamester; Daila Alena Raenck da Silva; Fernanda Vaz Dorneles; Fernando Santana Fraga; Paulo Ricardo Bobek; et al. (BMC, 2022)
Abstract Background There are many inequalities in terms of prevention and treatment for pregnant women with HIV and exposed children in low and middle-income countries. The Brazilian protocol for prenatal care includes rapid diagnostic testing for HIV, compulsory notification, and monitoring by the epidemiological surveillance of children exposed to HIV until 18 months after delivery. The case is closed after HIV serology results are obtained. Lost to follow-up is defined as a child who was not located at the end of the case, and, therefore, did not have a laboratory diagnosis. Lost to follow-up is a current problem and has been documented in other countries. This study analyzed factors associated with loss to follow-up among HIV-exposed children, including sociodemographic, behavioral, and health variables of mothers of children lost to follow-up. Methods This historical cohort study included information on mothers of children exposed to HIV, born in Porto Alegre, from 2000 to 2017. The research outcome was the classification at the end of the child's follow-up (lost to follow-up or not). Factors associated with loss to follow-up were investigated using the Poisson regression model. Relative Risk calculations were performed. The significance level of 5% was adopted for variables in the adjusted model. Results Of 6,836 children exposed to HIV, 1,763 (25.8%) were classified as lost to follow-up. The factors associated were: maternal age of up to 22 years (aRR 1.25, 95% CI: 1.09-1.43), the mother's self-declared race/color being black or mixed (aRR 1.13, 95% CI: 1.03-1.25), up to three years of schooling (aRR 1.45, 95% CI: 1.26-1.67), between four and seven years of schooling (aRR 1.14, 95% CI: 1.02-1.28), intravenous drug use (aRR 1.29, 95% CI: 1.12-1.50), and HIV diagnosis during prenatal care or at delivery (aRR 1.37, 95% CI: 1.24-1.52). Conclusion Variables related to individual vulnerability, such as race, age, schooling, and variables related to social and programmatic vulnerability, remain central to reducing loss to follow-up among HIV-exposed children.